A Fast Method of Cell Image Fusion Based on Content Analysis - JIAN Fu-rong; GAO Yu-dong; DING Bo; HE Yong-jun (Journal of Harbin University of Science and Technology)
The cells under the microscope are not in the same focal plane due to adhesion and overlap，and image fusion is required to obtain a clear image. The existing method is inefficient to fuse the whole image. In order to solve this problem，this paper proposes a method of cell image fusion based on content analysis. Firstly，the cell images at different depth positions under the same field of view were obtained by fast asynchronous image capture， and the images for fusion were screened out. Then the image was segmented，and the image content was divided into single cell，group cell and impurity through the VGG-16 model classifier，and then fused with different methods. Do not deal with garbage; Single cell image fusion was selected by contrast definition. Guided filtering was used to fuse the cluster cells. Finally，the fused cell contents are stitched together into a clear image as the final result. This method only performs complex fusion operation on the group cells，and effectively reduces the time complexity of the operation. The experimental results show that the proposed method has a 219% higher average fusion time and higher fusion efficiency than the existing methods.